2013
DOI: 10.1111/dsu.12268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Improvement of Striae Distensae in Korean Patients Using a Combination of Fractionated Microneedle Radiofrequency and Fractional Carbon Dioxide Laser

Abstract: Combination therapy of fractionated microneedle RF and fractional CO2 laser is a safe treatment protocol with a positive therapeutic effect on striae distensae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 19 publications
10
55
1
1
Order By: Relevance
“…FRM treatment level guidelines for striae distensae and atrophic scar [24][25][26] could provide a viable, minimally invasive treatment alternative for skin conditions commonly encountered in the dermatology practice. And they developed reproducible parameters and guidelines in order to most effectively treat a variety of skin conditions using FRM device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRM treatment level guidelines for striae distensae and atrophic scar [24][25][26] could provide a viable, minimally invasive treatment alternative for skin conditions commonly encountered in the dermatology practice. And they developed reproducible parameters and guidelines in order to most effectively treat a variety of skin conditions using FRM device.…”
Section: Resultsmentioning
confidence: 99%
“…Although a variety of laser and light sources have been used for the treatment of striae distensae, to date no definite 'gold standard' treatment modality has been determined. [24][25][26] A study of the FRM system on 30 female patients with moderate to severe striae distensae showed optimal clinical results with minimal side effects. 25 The panel contended that FRM system could be one of the suitable options for treating striae distensae and atrophic scar and suggested proper parameters which are shown on Table 5.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Ryu et al [8] conducted a study to evaluate the efficacy and safety of a combination therapy with fractionated microneedle RF and fractional CO 2 laser in the treatment of striae distensae. The study included 30 female patients with moderate to severe striae distensae who were evenly divided into three treatment groups: fractional CO 2 laser only (n = 10), microneedle RF only (n = 10), and combination therapy (n = 10).…”
Section: Striae Distensaementioning
confidence: 99%
“…Histologic examination showed a thickened epidermis and a clear increase in the number of collagen fibers in the microneedle RF-and fractional CO 2 combination-treated sites. The investigators concluded that the combination therapy of fractionated microneedle RF and fractional CO 2 laser is a safe treatment approach with a positive therapeutic effect on striae distensae [8].…”
Section: Striae Distensaementioning
confidence: 99%
“…As one of them, the distinct microstructural features, including anisotropic surface structure, have been demonstrated . Considering how SD develop, including dermal network ruptures and alignment to mechanical stretch, structural directionality or anisotropy could be expected . Although anisotropy is one of the major characteristics of SD, non‐invasive clinical studies on anisotropic properties remain rare.…”
Section: Introductionmentioning
confidence: 99%